Implementasi Supervisi Akademik Kepala Madrasah Terhadap Guru Di Madrasah Aliyah Islam Terpadu Darul Fikri Sidoarjo - Cindy Alfiah Oktriani; Fathul Fauzi (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2023)
The implementation of academic supervision in education has three stages, namely planning, implementation and evaluation. The role of the madrasa head in academic supervision of teachers is very important in every activity carried out at the madrasa. A supervisor has the ability to shape the characteristics and capacities of teaching staff, as well as coordinate and guide the growth and development of their abilities both individually and collectively. As a supervisor, the madrasa head supports teaching staff in preparing educational supervision programs, carrying out supervision using the correct approaches and supervision techniques, and evaluating the results of academic supervision. This research aims to find out how madrasa heads implement supervision of educators at MAIT Darul Fikri Sidoarjo. This research is qualitative research which aims to obtain an accurate, systematic and factual description of the characteristics, facts and relationships between the phenomena discussed. The methods used by the author in this research are interviews, observation and documentation. The subjects of this research were the head of the madrasah and the deputy curriculum educator. The collected data is then analyzed using data analysis. From the results of this research, the author can conclude that the head of the madrasah has carried out academic supervision in accordance with success indicators. The head of the madrasah guides educators in choosing teaching methods, directs educators in choosing teaching materials and conducting class visits